2019
DOI: 10.1021/acsami.8b21417
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Work Capacity of Electrochemical Artificial Muscles by Coiling Plies of Twist-Released Carbon Nanotube Yarns

Abstract: Twisted-yarn-based artificial muscles can potentially be used in diverse applications, such as valves in microfluidic devices, smart textiles, air vehicles, and exoskeletons, because of their high torsional and tensile strokes, high work capacities, and long cycle life. Here, we demonstrate electrochemically powered, hierarchically twisted carbon nanotube yarn artificial muscles that have a contractile work capacity of 3.78 kJ/kg, which is 95 times the work capacity of mammalian skeletal muscles. This record w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Kim and colleagues developed a three‐level hierarchical yarn consisting of twist, plying, and coiling to optimize contraction stroke. [ 354 ] Through their highly‐architectured structure they obtained a maximum tensile stroke of 15.1% for an applied stress of 36.4 MPa. Additionally, alternative materials systems have been explored, either to improve actuation performance or to increase manufacturability of electrochemically actuating yarns.…”
Section: Textile Actuators For Wearable Robotsmentioning
confidence: 99%
“…Kim and colleagues developed a three‐level hierarchical yarn consisting of twist, plying, and coiling to optimize contraction stroke. [ 354 ] Through their highly‐architectured structure they obtained a maximum tensile stroke of 15.1% for an applied stress of 36.4 MPa. Additionally, alternative materials systems have been explored, either to improve actuation performance or to increase manufacturability of electrochemically actuating yarns.…”
Section: Textile Actuators For Wearable Robotsmentioning
confidence: 99%
“…[8] Very recently, Kim et al demonstrated a multiplied CNT yarn muscle that provided a contractile work capacity of 3.78 kJ kg −1 . [23] However, the use of a liquid working system severely limits the practical application of the above-mentioned electrochemical yarn muscles.…”
mentioning
confidence: 99%
“…Kim et al have designed a hierarchically twisted electrochemical driven CNT yarn with a maximum tensile stroke of 15.1% and work capacity of 3.78 kJ/kg. [168]. This twisted and coil structure achieves the transformation of electrochemical driven CNT yarn from rotation actuation to stretching actuation (Figure 25b).…”
Section: Carbon Nanotubesmentioning
confidence: 96%